Socio-Economic Characteristics That Affect The Income Of Corn Farmers In Simalungun District - Sasmita Siregar; Sirojuzilam ,; Sumono ,; Tavi Supriana (JASc (Journal of Agribusiness Sciences), 2018)
This study was conducted to analyze how socio-economic characteristics affect the income of corn farmers in the research area. Determination of location is done purposively (purposive), that is Sidamanik District of Simalungun Regency with number of sample counted 30 farmer by using method of analysis of multiple linear regression model. The result of hypothesis test shows that simultaneously independent variable Age (X1), Land Area (X2), Experience of Berusahatani (X3), Total Dependent (X4), and Status of Land (X5) influence 98,70% to dependent variable Revenue (Y ). Partially significant variable influence income is age with regression coefficient value equal to - 279921,767 (tsig, 0,003), land area with regression coefficient value and + 1,615E7 (tsig 0,000)) and land status with regression coefficient value - 2,671E6 ( tsig 0,040), while the experience experience variable and the number of dependents have no significant effect. The most dominant independent variable affecting income is variable land area (X2) with value of Standardized Coefficients Beta equal to 1,127Keywords: Characteristics, Socio-economic, Income and Corn